THE EFFECT OF CAR, ROA, BI 7-DAY RATE, AND INFLATION ON NON-PERFORMING HOME FINANCING IN SHARIA GENERAL BANKS FOR THE 2016-2018 PERIOD - Rofadatul Hasanah; Dina Fitrisia Septiarini (Universitas Airlangga, 2020)
This study aims to determine the effect of Capital Adequacy Ratio, Return on Assets, BI 7-Day Rate, and Inflation towards Non Performing Financing Mortgages in Islamic commercial banks in Indonesia. The population of this study is the Islamic commercial banks in the period 2015-2019. The sample used is a saturated sample, which uses all Islamic banks as research samples. This research uses a quantitative approach using time series data. All variables use the percentage of growth and show the results of the level stas so that the technique used is Ordinary Least Square (OLS) regression analysis which is processed using E-Views 10 software. The results of this study indicate partially the Capital Adequacy Ratio and Return on Assets variables have a negative influence significant to NPF KPR. While BI 7-Day Rate and Inflation variables do not have an influence on NPF KPR. Even so, the Capital Adequacy Ratio, Return on Assets, BI 7-Day Rate, and Inflation variables simultaneously have a significant effect on the Non Performing Financing of Mortgages in Islamic commercial banks in Indonesia in the 2015-2019 period.Keywords: Capital Adequacy Ratio (CAR), Return on Assets (ROA), Inflasi, Kurs, Non Performing Financing (NPF), Home Ownership LoanREFFERENCE Adlan, M. Aqim. (2016). Penyelesaian kredit macet perbankan dalam pandangan Islam: Tinjauan regulasi kasus kredit macet akibat bencana alam. AN-NISBAH, 2(2), 145-186Akbar, Dinnul Alfian. (2016). Inflasi, Gross Domestic Product (GDP), Capital Adequacy Ratio (CAR), dan Finance to Deposite Ratio (FDR) terhadap Non Perfoming Financing (NPF) pada bank umum syariah di Indonesia. I-Economic, 2(2), 19-37.Asnaini, Sri Wahyuni. (2017). Faktor-faktor yang mempengaruhi Non Perfoming Financing (NPF) pada bank umum syariah di Indonesia tahun 2010-2013. JOCE IP, 11(1), 1-22.Astuty, Pudji dan Nisa Nurjanah. (2018). Analisis Pengaruh Financing to Deposit Ratio (FDR), Non Perfoming Financing (NPF), suku bunga dan bank size terhadap pembiyaan kpr syariah (studi kasus BUS di Indonesia dan Malaysia). Journal Ekonomi,20(3), 286-299.Auliani, Mia Maraya dan Syaichu. (2016). Analisis pengaruh faktor internal dan faktor ekternal terhadap tingkat pembiayaan bermasalah pada bank umum syariah di Indonesia Periode Tahun 2010-2014. Diponegoro Journal of Management, 5(3), 1-14.Bank Indonesia. (2018). Pengenalan inflasi. Diakses pada 11 November 2019. https://www.bi.go.id/id/moneter/inflasi/pengenalan/Contents/Default.aspxBank Indonesia. (2012). Surat Edaran Bank Indonesia perihal penerapan kebijakan produk pembiayaan kepemilikan rumah dan pembiayaan bermotor bagi Bank Umum Syariah dan Unit Usaha Syariah. Jakarta: Departemen Perbankan Syariah (DPbs) dan De[artemen Hukum (DHk).Biro Komunikasi Publik. (2019). Diakses pada 11 September 2019. https://www.pu.go.id/berita/view/16011/program-subsidi-rumah-kementerian-pupr-tahun-2018-targetkan-630-437-unit-rumahDendawijaya, Lukman. (2005). Manajemen Perbankan. Bogor: Ghalia Indonesia.Diansyah. (2016). Pengaruh faktor internal dan eksternal terhadap Non Perfoming Loan (Studi pada bank yang terdaftar di Bursa Efek Indonesia periode 2010-2014). Journal of Business Studies, 2(1), 9-13.Firdaus, Rizal Nur. (2015). Pengaruh faktor internal dan eksternal yang mempengaruhi pembiyaan bermasalah pada bank umum syariah di Indonesia. Jurnal El-Dinar, 3(1), 82-108.Haifa dan Dedi Wibowo. (2015). Pengaruh faktor internal bank dan makro ekonomi terhadap Non Performing Financing perbankan syariah di Indonesia: Periode 2010:01 – 2014:04. AN-NISBAH, 1(2), 29-44.Haris, Helmi. (2007). Pembiayaan kepemilikan rumah (sebuah inovasi pembiayaan perbankan syari’ah). Jumal Ekonomi Islam La_Riba, 1(1), 113-125.Hernawati, Herni dan Oktaviani Rita Puspitasari. (2018). Pengaruh faktor makroekonomi terhadap pembiayaan bermasalah. Journal of Islamic Finance and Accounting, 1(1), 29-44.Ikatan Akuntansi Indoensia. (2000). Standar akuntansi keuangan. Jakarta: Salemba Empat.Ikatan Bankir Indonesia. (2014). Mengelolah Kredit Secara Sehat. Edis Pertama. Jakarta: Gramedia Pustaka Utama.Isaev, Mirolim dan Mansur Masih. (2017). Macroeconomic and bank-specific determinants of different categories of non-perfoming financing in Islamics banks: Evidence from Malaysia. Munich Personal RePEc Archive Paper No 79719, 1-24. Retrieved from https://mpra.ub.uni-muenchen.de/79719/ Karl dan Fair. (2001). Pembayaran bunga tahunan dari suatu pinjaman, yang diperoleh. Yogyakarta: YKPN.Kasmir. (2009). Pengantar manajemen keuangan. Jakarta: Kencana.Kurniawan, Agung Widhi dan Zahra Puspitaningtyas. (2016). Metode penelitian kuantitatif. Yogyakarta: Pandiva Buku.Kusuma, Ervina Chandra dan A Mulyo Haryanto. (2016). Analisis pengaruh variabel kinerja bank (CAR, ROA, BOPO dan LDR), serta pertumbuhan kredit dan kualitas kredit terhadap Non Performing Loan (NPL). Diponegoro Journal of Management, 5(4), 1-13.Lidya, Rika. (2016). Dampak Inflasi, BI Rate, Capital Adequacy Ratio (CAR), Biaya Operasional Pendapatan Operasional (BOPO), terhadap Non Performing Financing (NPF) pada Bank Umum Syariah di Indonesia. Jurnal I-Finance, 2(1), 1-19.Meydianawathi, Luh Gede. (2003). Analisis perilaku penawaran kredit perbankan kepada sektor UMKM di Indoensia (2002-2006). Universitas Udayana Denpasar: Buletin Studi Ekonomi, 12(2). 135-147.Muhammad. (2005). Bank syariah problem dan proses perkembangan di Indonesia. Yogyakarta: Graha Ilmu. ______. (2005). Manajemen bank syariah. Yogyakarta: UPPAMP YKPN.Natsir, M. (2014) Ekonomi moneter dan perbankan sentral. Jakarta: Mitra Wacana Media.OJK. (2013). Laporan perkembangan keuangan syariah tahun 2013. Jakarta: Otoritas Jasa Keuangan.______. (2015). Statistik Perbankan Syariah. Jakarta: Departemen Perizinan dan Informasi Perbankan OJK Indonesia.______. (2015). Surat Edaran Otoritas Jasa Keuangan Surat Edaran BI NO.14/33/DPbs tentang penerapan kebijakan produk pembiayaan kepemilikan rumah dan pembiayaan kendaraan bermotor bagi bank umum syariah dan unit usaha syariah. Jakarta: Otoritas Jasa Keuangan.______. (2016). Statistik Perbankan Syariah. Jakarta: Departemen Perizinan dan Informasi Perbankan OJK Indonesia.______. (2016). Standar Produk Perbankan Syariah Musyarakah dan Musyarakah Mutanaqisah. Jakarta: Departemen Perbankan Syariah OJK Indonesia.______. (2017). Statistik Perbankan Syariah. Jakarta: Departemen Perizinan dan Informasi Perbankan OJK Indonesia.______. (2018). Statistik Perbankan Syariah. Jakarta: Departemen Perizinan dan Informasi Perbankan OJK Indonesia.______. (2019). Statistik Perbankan Syariah. Jakarta: Departemen Perizinan dan Informasi Perbankan OJK Indonesia.Pemerintah Indonesia. (2008). Undang-Undang Nomor 21 tahun 2008 perbankan syariah. Lembaran RI tahunn 2008 No 21. Jakarta: Sekretariat Negara.Rahmadani, Peni. (2016). Implikasi SBI, PDB, Inflasi, DPK, Total Aset, dan FDR pembiyaan KPR terhadap NPF Pembiayaan KPR Perbankan Syariah di Indonesia periode 2008-2015. Skripsi tidak diterbitkan. Jakarta: Universitas Islam Negeri Syarif Hidayatullah.Rakhmawati, Diah Nur. (2011). Analisis faktor-faktor yang mempengaruhi permintaan Kredit Pemilikan Rumah (KPR) pada bank umum di Indonesia tahun 2003-2010. Skripsi tidak diterbitkan. Surakarta: Universitas Sebelas Maret. Surakarta.Raysa, Siti. (2014). Pengaruh CAR, FDR, ROA, BOPO, Return Pembiayaan Profit Loss Sharing, BI Rate, dan Size terhadap Non Performing Financing pada Bank Umum Syariah Periode 2010-2013. Skripsi tidak diterbitkan. Yogyakarta: Universitas Islam Negeri Sunan Kalijaga.Sekretaris Kabinet RI. (2017). Diakses pada 10 September 2019. http://presidenri.go.id/program-prioritas-2/rumah-subsidi-untuk-masyarakat-berpenghasilan-rendah.htmlSudarsono, Heri. (2012). Bank dan lembaga keuangan syariah: Deskripsi dan ilustrasi. Yogyakarta: Ekosoria.Sunariyah. (2004). Pengantar pengetahuan pasar modal. Yogyakarta: AMP YKPN.Wardiantika, Lifstin dan Rohmawati Kusumaningtyas. (2014). Pengaruh DPK, CAR, NPF, dan SWBI terhadap pembiyaan murabahah pada bank umum syariah tahun 2008-2012. Jurnal Ilmu Managemen, 2(4), 1550-1561.Wardoyo, Paulus dan Endang Rusdiyanti. (2009). Faktor-faktor yang mempengaruhi Non Perfoming Loan bank perkreditan rakyat di eks karedidenan Semarang. J. Dinamika Sosbud, 11(2), 127-139.Yusof, Risylin Mohd, dkk. (2018). Macroeconomic shock, fragility and home financing in Malaysia: can rental index be the answer?. Journal of Islamic Accounting and Bussines Research, 9(1), 17-44. DOI 10.1108/JIABR-11-2015-0058.Yuwono, Febry A. (2012). Analisis pengaruh DPK, LDR, CAR, NPL, ROA dan SBI terhadap jumlah penyaluran kredit. Skripsi tidak diterbitkan. Semarang: Univeristas Diponegoro.